Magnetic Vestibular Stimulation (MVS). A research tool with possible implementation in rehabilitation of stroke-affected athletes – a review - Olszanecka, Monika; Olszanecki, Tomasz; Hanslik, Anna; Białek, Agata; Walczak, Agnieszka; Mendak, Magdalena (Quality in Sport, 2025)
Background: People often experience vertigo and other co-occurring effects caused by the action of a strong magnetic field, such as those found in the MRI generator. This effect is a result of vestibular stimulation of the inner ear, the mechanism being a magnetohydrodynamic force (Lorentz force) which is generated by the interaction between normal ionic currents in the endolymph of the inner ear and the strong magnetic fields of the static MRI devices. The result of the induction is magnetic vestibular stimulation (MVS). Aim of the study: This study aims to present potential of MVS in research of vestibular function, hemispatial neglect syndrome (HNS) and rehabilitation. Materials and Methods: PubMed and Google Scholar were searched using keywords including “magnetic vestibular stimulation”, “hemispatial neglect syndrome”, “caloric vestibular stimulation”, “galvanic vestibular stimulation”, “rehabilitation” in different combinations. Materials and Methods: PubMed and Google Scholar were searched using keywords including “magnetic vestibular stimulation”, “hemispatial neglect syndrome”, “caloric vestibular stimulation”, “galvanic vestibular stimulation”, “rehabilitation” in different combinations. Results: Several studies have been conducted using MVS, bringing new light to set-point adaptation of vestibular system. Moreover, MVS can induce spatial attention bias similar to HNS for at least one hour during session. Conclusions: MVS is a novel tool with many possibilities in e.g. vestibular research. Apart from research, it may have great potential in rehabilitation of patients with HNS – which could be beneficial also for athletes affected by stroke.